2015
DOI: 10.4103/0973-1296.165548
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic alkaloids from Menispermum dauricum inhibits BxPC-3 pancreatic cancer cells by blocking of Hedgehog signaling pathway

Abstract: Background:The Hedgehog (Hh) signaling pathway plays an important role in pancreatic cancer (PC) cells. Phenolic alkaloids from Menispermum dauricum (PAMD), a traditional Chinese medicine used for the treatment of immune disorders, have been reported to have antitumor activity recently.Objective:To investigate the efficacy and mechanism of PAMD against PC cell BxPC-3.Materials and Methods:F assay was used to assess cell proliferation inhibition of PAMD; the apoptotic induction and cell cycle arrest was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The tumor volume was calculated using the following formula: Volume=(4π/3) × (L/2) 3 , where L is the mean tumor length measured in 3 dimensions. It was observed that maximum tumor diameter was ~1.2 cm, and the tumor volume in the saline control group reached ~1,000 mm 3 at 21 days, which was in accordance with the results from our previous study (30). The weights of the tumor and spleen were measured.…”
Section: Methodssupporting
confidence: 92%
See 4 more Smart Citations
“…The tumor volume was calculated using the following formula: Volume=(4π/3) × (L/2) 3 , where L is the mean tumor length measured in 3 dimensions. It was observed that maximum tumor diameter was ~1.2 cm, and the tumor volume in the saline control group reached ~1,000 mm 3 at 21 days, which was in accordance with the results from our previous study (30). The weights of the tumor and spleen were measured.…”
Section: Methodssupporting
confidence: 92%
“…Dauricine, a bioactive component extracted from the moonseed rhizome, has demonstrated promising pharmacological attributes in clinical settings (24,30). It has long been used as a traditional Chinese medicine remedy for inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations